3-Deoxysappanchalcone Inhibits Skin Cancer Proliferation by Regulating T-Lymphokine-Activated Killer Cell-Originated Protein Kinase in vitro and in vivo - Fu, Xiaorong; Zhao, Ran; Yoon, Goo; Shim, Jung-Hyun; Choi, Bu Young; Yin, Fanxiang; Xu, Beibei; Laster, Kyle Vaughn; Liu, Kangdong; Dong, Zigang; Lee, Mee-Hyun (Frontiers in Cell and Developmental Biology, 2021)
Skin cancer is one of the most commonly diagnosed cancer worldwide and the survival rate of late stage is ranging 20-30% in 5 years. Thus, the investigation of novel therapeutic agents is of the utmost importance. The T-lymphokine-activated killer cell-originated protein kinase (TOPK), a serine-threonine kinase highly expressed and activated in skin cancer. The present study investigates the effect of 3-deoxysappanchalcone (3-DSC) plays as a TOPK inhibitor and suppresses SSL-induced skin hyperplasia and cancer growth. We have determined the overexpression of TOPK in skin cancer cells and 3-DSC directly bound to TOPK thus inhibited TOPK kinase activity as confirmed with TOPK wildtype and T42A/N172A mutant by pull-down assay. The treatment of 3-DSC suppressed the anchorage-dependent and -independent colony growth, and induced cell cycle arrest and apoptosis regulated their biomarkers. In vivo study, skin thickness and tumor size were reduced in the acute SSL-induced inflammation and SK-MEL-2 cell-derived xenografts mouse model by treated with 3-DSC. In addition, we found that 3-DSC decreased TOPK expression and its downstream effectors (ERK/RSK/c-Jun) in skin and tumor tissues by immunohistochemistry. Our results suggest that 3-DSC may function in both chemoprevention and chemotherapy by protecting UV-induced skin hyperplasia and inhibiting tumor growth via attenuating TOPK signaling.